Pneumonia After Cardiovascular Surgery: Incidence, Risk Factors and Interventions - Wang, Dashuai; Lu, Yang; Sun, Manda; Huang, Xiaofan; Du, Xinling; Jiao, Zhouyang; Sun, Fuqiang; Xie, Fei (Frontiers in Cardiovascular Medicine, 2022)
Postoperative pneumonia (POP) is prevalent in patients undergoing cardiovascular surgery, associated with poor clinical outcomes, prolonged hospital stay and increased medical costs. This article aims to clarify the incidence, risk factors, and interventions for POP after cardiovascular surgery. A comprehensive literature search was performed to identify previous reports involving POP after cardiovascular surgery. Current situation, predictors and preventive measures on the development of POP were collected and summarized. Many studies showed that POP was prevalent in various cardiovascular surgical types, and predictors varied in different studies, including advanced age, smoking, chronic lung disease, chronic kidney disease, cardiac surgery history, cardiac function, anemia, body mass index, diabetes mellitus, surgical types, cardiopulmonary bypass time, blood transfusion, duration of mechanical ventilation, repeated endotracheal intubation, and some other risk factors. At the same time, several targeted interventions have been widely reported to be effective to reduce the risk of POP and improve prognosis, including preoperative respiratory physiotherapy, oral care and subglottic secretion drainage. Through the review of the current status, risk factors and intervention measures, this article may play an important role in clinical prevention and treatment of POP after cardiovascular surgery.